2015
DOI: 10.1177/1932296815588108
|View full text |Cite
|
Sign up to set email alerts
|

Intrinsic Frequency and the Single Wave Biopsy

Abstract: Insulin resistance is the hallmark of classical type II diabetes. In addition, insulin resistance plays a central role in metabolic syndrome, which astonishingly affects 1 out of 3 adults in North America. The insulin resistance state can precede the manifestation of diabetes and hypertension by years. Insulin resistance is correlated with a low-grade inflammatory condition, thought to be induced by obesity as well as other conditions. Currently, the methods to measure and monitor insulin resistance, such as t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
21
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 15 publications
(21 citation statements)
references
References 30 publications
0
21
0
Order By: Relevance
“…The decoupling coordinates are represented as the relative height of decoupling at the dicrotic notch (RHDN) and the time of decoupling at the dicrotic notch (T 0 ). Previous studies [8,17] have indicated that LVEF (surrogate of LV contractility), LV-arterial coupling optimality, and central pulse wave velocity (a major determinant of arterial impedance and pulsatile afterload) can be evaluated as a function of IF parameters [9,10,12,14] (Figure 2). Previous results indicate that LV contractility and afterload can be approximated as a function of IFs (ω 1 , ω 2 , .…”
Section: Intrinsic Frequency Methodsmentioning
confidence: 99%
See 3 more Smart Citations
“…The decoupling coordinates are represented as the relative height of decoupling at the dicrotic notch (RHDN) and the time of decoupling at the dicrotic notch (T 0 ). Previous studies [8,17] have indicated that LVEF (surrogate of LV contractility), LV-arterial coupling optimality, and central pulse wave velocity (a major determinant of arterial impedance and pulsatile afterload) can be evaluated as a function of IF parameters [9,10,12,14] (Figure 2). Previous results indicate that LV contractility and afterload can be approximated as a function of IFs (ω 1 , ω 2 , .…”
Section: Intrinsic Frequency Methodsmentioning
confidence: 99%
“…Recently, we introduced the intrinsic frequency (IF) concept that reveals clinically relevant information about the dynamics of the left ventricle (LV), arterial system, and their interactions [7][8][9][10]. IF frequencies are operating frequencies based on the Sparse Time-Frequency Representation (STFR) [11], treating the LV combined with the aorta and the remaining peripheral arteries as a coupled dynamical system (heart + aortic tree), which is decoupled upon closure of the aortic valve [8,9,12].…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Their results indicated that ω 2 values were similar among younger participants but gradually diverged with age or progressive disease states. 12 , 15 In addition, the prior theoretical work showed that cardiac pulsatile power reaches a minimum at any given arterial stiffness at a heart rate where the difference between ω 1 and ω 2 is zero. 12 Thus, it was concluded that the total frequency variation (Δω=ω 1 −ω 2 ) may provide an additional novel measure of optimal ventricular vascular coupling and vascular health.…”
mentioning
confidence: 99%